Comunicación y desinformación en tiempos de COVID-19 en Ecuador (Monográfico) - Bayas Ramírez, Krushenka (2021)
The COVID-19 pandemic exposed not only the structural problems of health systems on a global scale, but also problems in effective communication of the crisis and how to avoid or at least contain it. These problems were also affected by the proliferation of misinformation on topics as varied as treatments, symptoms, origins or ways to prevent its spread. Although, the verification platforms fulfill an important task to counteract the so-called fake news, the amount of information and misinformation that circulated in the first months of the pandemic was so great that an effort is needed that covers more fronts to be able to communicate efficiently the phenomenon and its different edges. The verifications made by Ecuador Chequea during the first semester of 2020 were classified under qualitative criteria such as the emotions they provoke or the subject to which they refer and through the use of Information Design and Data Visualization tools, graphic pieces were developed that show the relationship between the production of information and the development of the pandemic in Ecuador. Once this was done, it was necessary to communicate the findings and this work presents the development and quantitative results of the communication campaign on social networks designed to help educate the general public to distinguish misinformation.